Transformation and Design Thinking: Perspectives on sustainable change, company resilience and democratic leadership in SMEs - Daria Habicher; Greta Erschbamer; Harald Pechlaner; Linda Ghirardello; Maximilian Walder (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
This paper focuses on Design Thinking as a tool for initiating transformation processes both for the enhancement of company resilience, involving challenges connected to current trends such as digitalization and democratic leadership, as well as for the restructuring of a sustainable socio-ecological company organization. Primary findings of this explorative study show that Design Thinking is a suitable method to promote digital, democratic, and innovative business and leadership transformation, but that it is not primarily operationalized in the context of a further-reaching socio-ecological transformation towards more sustainability.
Keywords: 330; Company resilience; Democratization; Design Thinking; Digitalization; Leadership; SMEs; Socio-ecological transformation; Sustainability; Transformation processes